Banco didáctico de ensayos a torsión (2020)
This work presents the process followed to obtain the manufacturing and tuning of a didactic bench that performs torsion tests on standardized specimens according to the ASTM-E143 standard. The first activity was that a sensitivity analysis was performed on the prototype turning angle and torque measurement system, and this was carried out based on the theory of error; having these criteria, the error made in the measurement system was determined. Then the electronic devices required for the measurements were purchased. Following this, the required parts were manufactured in the local market, guided by the detailed design drawings, to subsequently carry out the assembly, adjustments and calibration of the prototype were carried out, and tests were carried out to verify correct operation. . Finally, pedagogical material was made with a step-by-step of how to carry out the tests and a Maintenance Manual to guarantee a longer useful life for the prototype.